2014
DOI: 10.1007/s12298-014-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

The physiological response of Artemisia annua L. to salt stress and salicylic acid treatment

Abstract: Salinity has a great influence on plant growth and distribution. A few existing reports on Artemisia annua L. response to salinity are concentrated on plant growth and artemisinin content; the physiological response and salt damage mitigation are yet to be understood. In this study, the physiological response of varying salt stresses (50, 100, 200, 300, or 400 mM NaCl) on A. annua L. and the effect of exogenous salicylic acid (0.05 or 0.1 mM) at 300-mM salt stress were investigated. Plant growth, antioxidant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…Numerous reports have shown that methyl jasmonate (MeJA), ABA and salt stress are crucial mediators in AN biosynthesis by activating downstream regulatory genes (Jing et al, 2009; Li et al, 2014; Maes et al, 2011; Paul and Shakya, 2013; Zhou and Memelink, 2016). Hence, we examined whether AaTCP15 was regulated by these treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have shown that methyl jasmonate (MeJA), ABA and salt stress are crucial mediators in AN biosynthesis by activating downstream regulatory genes (Jing et al, 2009; Li et al, 2014; Maes et al, 2011; Paul and Shakya, 2013; Zhou and Memelink, 2016). Hence, we examined whether AaTCP15 was regulated by these treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity-driven reduction in plant growth has been reported in several plant species such as Acacia auriculiformis (29), Sesbania aegyptiaca and Sesbania grandiflora (30), Acacia nilotica (31), Lotus glaber (32), Trifolium alexandrinum (33); Linum usitatissimum (34), Trigonella foenumgraecum (28) and Artemisia annua (10); however in all these cases mycorrhiza-inoculated plants performed better than uninoculated plants. The beneficial effect of mycorrhizal colonization on plant growth under saline condition has been documented as an impact of improved uptake of soil nutrients by mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Further, excessive salts in soil could induce osmotic, ionic, and oxidative stresses that severely affect plant growth. Several researchers have demonstrated that mycorrhizal fungi mitigate negative effects of salinity stress and promote plant growth (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress was given in 5 concentrations viz . 25mM, 50mM, 75mM, 100mM and 125mM NaCl by irrigating the test plant pots with 100ml of NaCl solution [25] constantly for 10 days and at every alternate day during the complete treatment cycle of 30 days. To prevent the plants from osmotic shock, treatment was started with lower concentrations, gradually increasing the concentration daily, until each group.…”
Section: Methodsmentioning
confidence: 99%